Quality of life of elderly people living with family and in old age home in Morang District, Nepal - Shrestha, Menuka; KC, Heera; Bhattarai, Prem; Mishra, Anjali; Parajuli, Surya B. (BIBECHANA, 2018)
Introduction: Nepal like many other developing countries in the world is witnessing the rapid ageing of population. Quality of life (QOL) of elderly people is becoming even more relevant towards an ageing society. In Nepal, less is known regarding special needs and quality of life of elderly people either in familial situations or in old age residences. Objectives: The present study was undertaken to assess and compare the quality of life of elderly living with the family and in old age home. Methodology: A Cross sectional descriptive study was conducted from October 2016 to April 2017 among elderly population aged 60 years and above. A total of 50 elderly people were enrolled from old age home (OAH) using total enumeration sampling technique and equal number of sample was selected from the family setting. QOL of elderly was assessed using WHOQOL-BRIEF questionnaire after taking informed consent from the participants. Data was analyzed using SPSS. Results: The mean scores of QOL domains were better among the age group 60-70 years, males, married, literates and who had children. The mean scores of QOL in physical, psychological and environmental domains were better in elderly living with the family than living in OAH. Low scores were found on social domain among elderly compared to other domain irrespective of their residence. Conclusion: QOL score among elderly is average, while social relationship domain of QOL scores was found to be low. Social activities should be expanded for these residents in order to promote social health. The QOL which each individual possesses is very important in all aspects be it physical, psychological, social & environmental. Furthermore, programs that help elderly people live in their own homes and social environments should be promoted. BIBECHANA 16 (2019) 221-227